2014
DOI: 10.1074/jbc.m113.534263
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Cell Heparan Sulfate 6-O-Sulfotransferases Regulate an Angiogenic Program Induced by Heparin-binding Epidermal Growth Factor (EGF)-like Growth Factor/EGF Receptor Signaling

Abstract: Background: Numerous angiogenic growth factors depend on heparan sulfate for their activity. Results: Heparan sulfate 6-O-sulfotransferases induce angiogenesis through HB-EGF/EGFR signaling and angiogenic cytokine expression in ovarian cancer cells. Conclusion: Ovarian cancer cell 6-O-sulfation levels influence angiogenic responses. Significance: HS6ST inhibitors and HS mimetics should be explored in the development of new anti-angiogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 41 publications
2
39
1
1
Order By: Relevance
“…Following the 6-O-sulfation of HS, HSPGs participate in the regulation of numerous signaling pathways by binding and activating cytokines. Growth factors including epidermal growth factor (EGF), fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) are dependent on the 6-O-sulfation of HS to assemble tri-molecular signaling complexes (HS-growth factor-receptor) for signal transduction (29)(30)(31)(32). Previous emerging evidence has indicated that HS6ST2 is a critical factor involved in regulating processes of angiogenesis and epithelial-mesenchymal transition (EMT) during carcinogenesis.…”
Section: Hs6st2 Expression ------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…Following the 6-O-sulfation of HS, HSPGs participate in the regulation of numerous signaling pathways by binding and activating cytokines. Growth factors including epidermal growth factor (EGF), fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) are dependent on the 6-O-sulfation of HS to assemble tri-molecular signaling complexes (HS-growth factor-receptor) for signal transduction (29)(30)(31)(32). Previous emerging evidence has indicated that HS6ST2 is a critical factor involved in regulating processes of angiogenesis and epithelial-mesenchymal transition (EMT) during carcinogenesis.…”
Section: Hs6st2 Expression ------------------------------------mentioning
confidence: 99%
“…In thyroid carcinomas, HS6ST2 was identified as a target gene of twist family bhlh transcription factor 1, a critical regulator of EMT (10,35). Inhibition of H6ST2 in tumor cells impairs cell migration, invasion, tubule formation, and may reverse EMT (10,13,32). Notably, previous reports revealed that the specific inhibition of HS6ST2 by a high molecular weight Escherichia coli K5-derived heparin-like polysaccharide (K5-NSOS), prevented tumor progression in a mouse model of breast cancer metastasis (15).…”
Section: Hs6st2 Expression ------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 remaining down-regulated transcripts included 2010111I01Rik, Sorbs2, Phf17, Ubr3 and Fth1 , catalogued under the term GO:0046914 ( transition metal ion binding ). On the other hand, the 3 up-regulated genes persisting until p28 were Hs6st2 , a heparan-sulfate sulfotransferase linked to EGF-like induced angiogenesis in OC cells [28], Hmga1 , coding for a non-histone chromosomal protein recently proposed as a diagnostic urine marker in serous epithelial OC [29] and Mmp2 , a matrix metallopeptidase implicated in OC metastasis [30]. Interestingly, though high Malat1 expression has been linked to cell proliferation and metastasis, a recent study suggest a tumor-suppressor role of Malat1 in gliomas through inhibition of ERK/MAPK signaling and Mmp2 -mediated invasiveness [31], findings consistent with its down-regulation in our model.…”
Section: Resultsmentioning
confidence: 99%
“…The induced expression of specific sulfation motifs is associated with human diseases, including certain cancers, 16,17 Alzheimer’s disease, 18 osteoarthritis, 19,20 malaria, 21,22 herpes, 23 and macular corneal dystrophy, 24 but surprisingly, pharmacological tools for manipulating GAG sulfation have been lacking. Cellular sulfation levels can be modulated genetically or by using sodium chlorate, which inhibits PAPS synthetase.…”
Section: Introductionmentioning
confidence: 99%